y = -6
Okay lets substitute x = 0
7 x 0 + 2y = -12
solve the equation for y
y = -6
Answer:
2×3+3
6+3
9
I think this is your answer
Answer:
128 my answer needs to be long so im just gonna span a little
Answer:
‹A = 141°
‹B = 28°
‹C = 11°
*These angles are rounded to the nearest whole*
Step-by-step explanation:
Because you are only given sides you can find an individual angle measures with the inverse law of cosines.
Remember the side opposite of the angle corresponds to that angle.
a² = b² + c² - 2bc cos(A) →
A = cos⁻¹ (a² - b² - c² / -2bc)
b² = a² + c² - 2ac cos(B) →
B = cos⁻¹ (b² - a² - c² / -2ac)
c² = a² + b² - 2ab cos(C) →
C = cos⁻¹ (c² - a² - b² / -2ab)